Complete genome sequence of Thauera aminoaromatica strain MZ1T. Issue 3 (May 2012) - Jiang, Ke; Sanseverino, John; Chauhan, Archana; Lucas, Susan; Copeland, Alex; Lapidus, Alla; Glavina Del Rio, Tijana; Dalin, Eileen; Tice, Hope; Bruce, David; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract Thauera aminoaromatica strain MZ1T, an isolate belonging to genusThauera, of the familyRhodocyclaceae and the class theBetaproteobacteria, has been characterized for its ability to produce abundant exopolysaccharide and degrade various aromatic compounds with nitrate as an electron acceptor. These properties, if fully understood at the genome-sequence level, can aid in environmental processing of organic matter in anaerobic cycles by short-circuiting a central anaerobic metabolite, acetate, from microbiological conversion to methane, a critical greenhouse gas. Strain MZ1T is the first strain from the genusThauera with a completely sequenced genome. The 4, 496, 212 bp chromosome and 78, 374 bp plasmid contain 4, 071 protein-coding and 71 RNA genes, and were sequenced as part of the DOE Community Sequencing Program CSP_776774.